1993
DOI: 10.1007/bf00301048
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional biomechanical properties of the human cervical spine in vitro

Abstract: Our aim was to determine the biomechanical properties of the normal human cervical spine under physiological static loads. The three-dimensional displacements under three pure moments: flexion-extension, left-right lateral bending and left-right axial torsion--were measured in 56 intact functional spinal units (FSUs) taken from between C2 and C7 in 29 human cadavers. For each mode of loading, load-displacement curves were plotted. Then we calculated each neutral zone, range of motion, neutral zone ratio, ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…A study on the human lumbar spine found that torsional strains rather than compressive loads are likely to be responsible for intervertebral disc degeneration 43 . The difference in both the pattern and the magnitude of loading between large and small breed dogs may in part explain why cervical complaints in large‐breed dogs tend to occur in the caudal cervical spine 44,45 . Whereas our study was not designed to address this question directly, further studies, possibly involving a combination of finite element modeling and direct validation in cadaveric specimens, should be undertaken to more completely explore this potentially intriguing relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the human lumbar spine found that torsional strains rather than compressive loads are likely to be responsible for intervertebral disc degeneration 43 . The difference in both the pattern and the magnitude of loading between large and small breed dogs may in part explain why cervical complaints in large‐breed dogs tend to occur in the caudal cervical spine 44,45 . Whereas our study was not designed to address this question directly, further studies, possibly involving a combination of finite element modeling and direct validation in cadaveric specimens, should be undertaken to more completely explore this potentially intriguing relationship.…”
Section: Discussionmentioning
confidence: 99%
“…43 The difference in both the pattern and the magnitude of loading between large and small breed dogs may in part explain why cervical complaints in large-breed dogs tend to occur in the caudal cervical spine. 44,45 Whereas our study was not designed to address this question directly, further studies, possibly involving a combination of finite element modeling and direct validation in cadaveric specimens, should be undertaken to more completely explore this potentially intriguing relationship. We found that the ratio of CM/PM increased for the caudal cervical levels for left/right lateral bending and decreased for left/right axial rotation.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a previous report in humans, the ratio of the CM to the PM in left/right lateral bending and left/right axial rotation was 0.37 and 0.46, respectively. 14…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the extent of the coupling effect, the dimensionless ratio of CM to PM is reported. [14][15][16] For dogs, no such information is available. Recommendations for mechanical testing protocols have been made.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have focused on the biomechanics of the thoracic spine, because prior research mainly focused on the lumbar [14] and the cervical spine [57]. This is due to the fact that chronic degenerative diseases of the thoracic spine are reported to have a lower incidence and therefore seem to be clinically of lower importance [8].…”
Section: Introductionmentioning
confidence: 99%